2011
DOI: 10.3390/en4101624
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Optimization Modeling of Energy Systems Planning and GHG Emission Mitigation under Uncertainty

Abstract: Abstract:Energy is crucial in supporting people's daily lives and the continual quest for human development. Due to the associated complexities and uncertainties, decision makers and planners are facing increased pressure to respond more effectively to a number of energy-related issues and conflicts, as well as GHG emission mitigation within the multiple scales of energy management systems (EMSs). This quandary requires a focused effort to resolve a wide range of issues related to EMSs, as well as the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 304 publications
(282 reference statements)
0
44
0
Order By: Relevance
“…There are many different models available in the literature. Jebaraj and Iniyan [13], Zeng et al [14] and Bhattacharyya [15] surveyed many different energy system models, modelling approaches and their applications. Connoly et al [16] analysed and compared different existing energy system models and concluded that there are no models that are suitable for all aspects of integrated renewable energy and therefore the tool of choice will depend on the 100 specific scenario being considered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different models available in the literature. Jebaraj and Iniyan [13], Zeng et al [14] and Bhattacharyya [15] surveyed many different energy system models, modelling approaches and their applications. Connoly et al [16] analysed and compared different existing energy system models and concluded that there are no models that are suitable for all aspects of integrated renewable energy and therefore the tool of choice will depend on the 100 specific scenario being considered.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Note that the subscripts for the flow directions are now the opposite of those that appear in equation 14.…”
mentioning
confidence: 99%
“…The results, obtained in the process of developing mathematical models, should be the foundation for improving their constructions and structural schemes [14,15], for optimization of the modes of their operation, for reducing harmful impact [16] and finding new approaches and solutions [17].…”
Section: Scientific Literature Analysis and The Problem Statementmentioning
confidence: 99%
“…In [17], decision architecture for tri-level production process is proposed for implementing "environmental-benign" and low emission manufacturing industry. Optimization based approaches for low-carbon energy systems planning under uncertainty are comprehensively reviewed in [18]. In traditional single level optimization methods, emission constraints are incorporated in the economic dispatch (ED) model, so that the actual emission corresponding to the optimal solution will not violate the pre-specified value.…”
Section: Introductionmentioning
confidence: 99%